The visual acuity impairment as the only sign of cerebral anursms – case report - Kopacz, Dorota; Maciejewicz, Piotr; Dróbecka-Brydak, Ewa; Prokopienko, Marek; Brożek-Szymańska, Kinga; Kęcik, Dariusz; Marchel, Andrzej; Jaworski, Maciej (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
Cerebral aneurysms are the most common reason of subarachnoid haemorrhage at the age of 50 – 60. Though the results of such haemorrhage are severe (high morbidity and mortality), it is quite often, the first noticeable sign of the problem. Previous symptoms i. e. headache, ophthalmic disturbances, temporary neurological symptoms are often passed over. The authors present the case of a young woman with cerebral aneurysms, in which the visual acuity impairment was the only symptom of the disease.